Propuesta de mejora en los procesos de producción de claveles en la microempresa FLOR DEL CAMPO en el barrio Zumbalica. - Guaña Benavides, Jennifer Katherine (2019)
The study of the improvement of processes in a production micro enterprise is the essential part to adapt the processes and reduce resources that are made in the operations, which help to have an adequate planning and thus be able to project to the future in an effective and efficient way. In the FLOR DEL CAMPO micro-enterprise, the aim is to optimize production, through the study of improvement in the post-harvest processes area, thus obtaining a production of very good quality carnations. For the development of this project, the text of Deming Towards Continuous Improvement is used as a bibliographic and practical source, which allows to represent the current and future situation, through the data collection with the selected measurement technique and taking into account the operator's working conditions of the, giving fulfillment to the activities proposed in this project allowing to analyze and establish opportunities for improvement. The proposal presented in this research details each of the identified problems within the post-harvest area and at the same time the shortcomings that exist within the harvest, which means that the process is not adequate to obtain a carnation that meets all the requirements necessary to be considered carnation export. Finally we will proceed to detail the obtained results in relation to the same improvement proposal that will increase productivity in the micro-enterprise and therefore to offer a quality carnation, with this the Flor del Campo micro enterprise optimizes both administrative and human resources, being they are the main beneficiaries of this proposal, and the indirect beneficiaries will be their clients and workers because the micro-enterprise will be able to offer their demand in less time and with better quality in the product.